Reversibility in the Educational Trajectories of Russian University Students: A Questioning Approach - V. F. Pugach; V. L. Petrov (Высшее образование в России, 2025)
The article presents the results of a sociological study devoted to the analysis of the structure of admission to universities by level of education. The empirical basis of the study is the data of educational statistics of the Ministry of Education and Science of the Russian Federation. The purpose of the article is to analyze the formation of student contingents of universities, taking into account the features of educational trajectories along which students come to the university, including those who already have higher education. The diversity of educational trajectories that appeared after Russia’s transition to multi-level higher education is shown. The results of a comparative analysis of the formation of student contingents of different levels of higher education (bachelor’s degree, specialist’s degree, master’s degree), public and private universities are shown. Particular attention is paid to individuals entering a second or subsequent higher education. That is, such options for educational trajectories when people with higher education re-enter not only the same level of higher education that they received earlier, but also other levels that are lower than the ones they already have. These flows, called reversible, are given quantitative assessments, their scales and vectors of dynamics are described. This is the novelty of the work.A conclusion is made about the emergence in post-Soviet Russia of a new, fairly stable channel for the formation of student contingents due to the so-called reversible students, a comparative analysis of state and private universities is given by the scale of reversible flows, their changes in dynamics.